The Influence of Liquidity Ratio (CR), Solvency Ratio (DAR), Activity Ratio (ITO), Board Gender Diversity (BGD), and Independent Commissioner Composition (KI) on Profitability (NPM) of Non-Financial Companies on the Kompas 100 Index - Soliatun; Patrick Kevin Aritonang (Economic Reviews Journal, 2026)
This study aims to analyze the effect of Liquidity (Current Ratio/CR), Solvency (Debt to Asset Ratio/DAR), Activity (Inventory Turnover/ITO), Board Gender Diversity (BGD), and Independent Commissioner Composition (KI) on Profitability (Net Profit Margin/NPM) in non-financial companies listed on the Kompas100 Index in 2024, with an observation period of 2021-2024. In an era of economic uncertainty and increasingly fierce business competition, optimizing company value is crucial, where profitability is a key indicator of financial performance that reflects operational efficiency and investment attractiveness. This study adopts a quantitative approach using secondary data from the annual financial reports of non-financial companies in the Kompas100 Index for the 2021-2024 period obtained from the Indonesia Stock Exchange (IDX). Research observations were selected using a purposive sampling technique based on certain criteria adjusted to the variables being tested, including companies that publish complete financial reports and have female board directors and independent commissioners. This study uses unbalanced panel data with an observation period of 2021–2024. The analytical method used is panel data regression with the Pooled Least Squares (OLS) approach in the Eviews application. The results of this study are expected to provide empirical understanding of the influence of financial ratios (CR, DAR, ITO) and corporate governance aspects (BGD, and KI Composition) on profitability (NPM). Specifically, this study will examine whether CR, ITO, and BGD have a positive effect, while DAR and KI have a negative effect on NPM.